Development, validation, and reliability of athletes` resilience index - Khalid, N. H. M.; Rasyid, N. M.; Ahmady, Y. (Pedagogy of Physical Culture and Sports, 2022)
Background and Study Aim: The ability to turn back from stressful experiences quickly and efficiently is essential for any athlete who performs in high-level competition. Measuring the degree to which athletes deal with adversity, setbacks, and failure has become the area of concern in the field of resilience. The main aim of the study was to develop, validate and test the reliability of a new index of measurement that can evaluate the level of athletes` resilience. Material and Methods: The first phase of the study is developing 37 items of the Athletes Resilience Index (ARI-37) based on previous qualitative data. Meanwhile, in the second phase, the study focused on establishing the Confirmatory Factor Analysis, convergent validity, and construct reliability of the index. The sample consisted of 351 Performance Development athletes who represent the state of Perak, Malaysia in the Malaysian Games (SUKMA) 2022. Results: Confirmatory Factor Analysis retained five risk issues in sports setting including performance, change, behavioral, psychological, and interpersonal. However, instead of 37 items, the Confirmatory Factor Analysis confirmed 26 items only. Most of the factors in ARI-26 yielded a high coefficient value of convergent validity (>0.5). Construct reliability of the index was also sufficient (0.44 to 0.62). Conclusions: The development of ARI-26 will allow researchers to better capture the unique aspects of resilience in the sports context. Thus, the Athletes` Resilience Index (ARI-26) is revealed to be a reliable instrument for the assessment of resilience levels in high-level athletes.